The Ideological Embodiment on Nadiem Makarim’s Speech: A Critical Discourse Analysis - Ani Maghfiroh; Sulis Triyono (Indonesian Journal of EFL and Linguistics, 2020)
This study purposes to uncover the symbolic ideology and the structures of the speech discourse delivered by the current new-inaugurated educational and cultural minister; Nadiem Makarim on National Teacher’s Day. The descriptive qualitative method was employed to shed a light on the interpretation and finding of the study whilst the model of van Dijk in CDA was used to identify and answer the problems. The data were totally elicited from the speech text whilst it was as well used as subject of the study. The documentation method was applied and the data were afterwards expounded descriptively. The finding denotes that of the speech discourse’s structures including macro, micro, and supra, the speech is perceived to have certain language style usage by underlying topic of speech on conveying the mission of providing a change towards Indonesia’s Better Education. In addition, the ideology is as well indicated in ways behind the structures organized. The macro structure puts the ideology beneath the theme and the topic which are in the forms of ideology purposed as system of beliefs and system of actions. In essence, the tendency of the ideology lies on the aspect of speech theme in which it was utilized to invite (deliberately aimed) the educators and all parts getting involved in education realm and to believe and to act as what was expected.